Perancangan Arsitektur Enterprise Pada Yayasan Pembangunan Pondok Pesantren Bustanul Ulum Menggunakan Framework Gartner - Irawan, Asep; Widi Nugroho, Handoyo; Purnomo, Hendri (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
This study focuses on the design of an information system architecture at Yayasan Pembangunan Pondok Pesantren Bustanul 'Ulum using the Gartner Enterprise Architecture model. The main objective of this design is to develop and implement information technology that can enhance the efficiency and effectiveness of business processes and administrative management at the foundation. The design stages include analyzing environmental trends and business strategies, developing requirements, principles, and architectural models, as well as designing a future architecture that encompasses business, information, and technology architecture. The analysis results indicate an urgent need to upgrade IT facilities, develop documentation and authentication systems, and integrate the laboratory system. The implementation of this architecture is expected to support the foundation's goals in providing quality education and improving school management performance. Â